Performance Improvement Through Motivation: Commitment Parallel Mediation Model - Limiao Limiao; Rahayu Lestari (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2022)
Purpose The study describes a parallel mediation model of improving performance through motivation with the mediation of commitment (affective, normative, and continuation). This provides an overall picture of how three commitment dimensions and their variations mediate the relationship between motivation and performance. Methodology A sample of 105 respondents from online motorcycle taxi drivers in Jakarta Indonesia was taken using a convenience sampling technique. The method of testing the hypothesis is through the macro process model no 4 with SPSS and Process v3.5. Findings The results found that total commitment (all three combined/ unidimensional) was shown to mediate the relationship between extrinsic and intrinsic motivation for performance. Meanwhile, when the commitment is multidimensional, only affective commitment mediates the relationship between extrinsic and intrinsic motivation to performance.. Suggestion This finding has implications for companies to maintain employee commitment, especially affective commitment.